Polydatin Inhibits Cell Viability, Migration, and Invasion Through Suppressing the c-Myc Expression in Human Cervical Cancer - Bai, Longchang; Ma, Yingkang; Wang, Xue; Feng, Qiongni; Zhang, Zhining; Wang, Sijie; Zhang, Huijie; Lu, Xinyu; Xu, Yonghui; Zhao, Erhu; Cui, Hongjuan (Frontiers in Cell and Developmental Biology, 2021)
Polydatin, an active ingredient from the roots of Polygonum cuspidatum, is considered to have protective effects on the cardiovascular system and liver. In this study, we demonstrated that polydatin has antitumor activity against human cervical cancer. Polydatin efficiently inhibited cervical cancer cell proliferation by regulating cell cycle-related proteins including p21, p27, CDK2, CDK4, Cyclin D1, and Cyclin E1. Furthermore, polydatin suppressed cell invasion and migration by regulating epithelial–mesenchymal transition (EMT) markers, including E-cadherin, N-cadherin, Snail and Slug. The c-Myc, as a proto-oncogene, is considered to be closely associated with the proliferation and metastasis of tumor cells. After polydatin treatment, the protein expression of c-Myc showed a significant decrease. Based on these data, we overexpressed c-Myc in cervical cancer cells and observed that the overexpression of c-Myc rescued the inhibitory effect of polydatin on cell proliferation and metastasis. These results indicated that polydatin can inhibit cell proliferation and metastasis through suppressing the c-Myc expression in human cervical cancer.